Optimising Operational in Interior Design Business Process at PT. Kreasindo Blessing House - Maulana, Fakhrian; Okdinawati, Liane (Jurnal Multidisiplin Indonesia, 2024)
This study aims to improve and streamline business procedures at PT. Kreasindo Blessing House . The study's history is thoroughly covered throughout the paper, emphasising the topic's importance and how it relates to the business's operations. This study's primary focus is on the problem of project delays, which has been seriously hurting PT. Rumah Kreasindo Berkah's finances. It is a fresh topic of inquiry because the efficiency advances of the interior design industry have yet to be thoroughly studied. Research to date has yet to address this sector's potential for optimisation. A combination of observational methods and interviews with upper management were used in this study. The study includes an analysis of the complete production flow and internal staff members of PT. Kreasindo Blessing House . The study produces new business procedures and well-thought-out solutions to improve productivity and shorten project turnaround times. The results will provide suggestions for increasing productivity and reducing project implementation delays. Each organisation applies efficiency measures differently, and theoretical ideas might not match actual situations. This study emphasises how crucial it is to modify efficiency tactics to fit the particular circumstances of each business, providing insightful information to academics and business professionals.